(untitled) (Publicacions de la Universitat de València, 2024)
This collection of essays brings together an international group of scholars who discuss various facets of the American South in popular culture, literature, the arts, and throughout history. It includes reflections on place, on the importance of memory in shaping individual identity, and on race, class and gender. All the contributions confirm Howard’s Zinn’s idea that the South “is not damnable, but marvelously useful, as a mirror in which the nation can see its blemishes magnified, so that it will hurry to correct them.” This volume sheds light on the “marvelous” sides of the South though it does not overlook its darker ones, thus making it possible to better understand this peculiar region. En esta colección de ensayos de investigadores de varios países se analizan diversas facetas del Sur de Estados Unidos en la cultura popular, la literatura y las artes a lo largo de la historia. Incluye reflexiones sobre el lugar, sobre la importancia de la memoria en la conformación de la identidad individual y sobre raza, clase social y género. Todas las contribuciones confirman la idea de Howard Zinn de que el Sur “no es condenable, sino maravillosamente útil, como espejo en el que la nación puede ver magnificadas sus imperfecciones, para que se apresure a corregirlas”. Este volumen arroja luz sobre los aspectos “maravillosos” del Sur, aunque no pasa por alto sus elementos más oscuros, lo que permite comprender mejor esta peculiar región.